Battery diaphragm and preparation method thereof

By using the combination of end amino polyethylene oxide coated oxide electrolyte and polymer electrolyte in the lithium-ion battery separator, the problem of unstable contact between LATP and metallic lithium negative electrode is solved, and the ionic conductivity and cycling performance of lithium metal batteries are improved.

CN119651052APending Publication Date: 2025-03-18LUCKY FILM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820892.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are unstable when LATP comes into contact with the metal lithium negative electrode, resulting in a decrease in structural stability and a decrease in ionic conductivity, affecting the cycling performance of lithium metal batteries.

Method used

The oxide electrolyte is coated with end amino polyethylene oxide (such as titanium aluminum lithium phosphate) and is used in conjunction with polymer electrolyte (such as polyethylene epoxy) to form a coating to improve the ionic conductivity and contact stability of the membrane.

Benefits of technology

It effectively improves the ionic conductivity and cycling performance of lithium metal batteries, enhances the contact stability between the separator and the metal lithium negative electrode, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183078550000081
    Figure BDA0005183078550000081
  • Figure BDA0005183078550000091
    Figure BDA0005183078550000091
  • Figure BDA0005183078550000092
    Figure BDA0005183078550000092
Patent Text Reader

Abstract

The invention discloses a battery diaphragm which comprises a base membrane and a coating located on at least one surface of the base membrane, the coating comprises the following raw materials in parts by weight: 100 parts of oxide electrolyte; 1 to 10 parts of polymer electrolyte; 1 to 10 parts of amino-terminated polyoxyethylene; 1-5 parts of a coupling agent; 5 to 15 parts of other auxiliary agents; and 100 to 400 parts of water. The battery diaphragm can effectively improve the ionic conductivity and the cycle performance of the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a battery separator of a lithium metal battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high specific capacity, long cycle life, and green environmental protection. Among them, lithium metal is the negative electrode material with the highest known specific capacity, with a theoretical specific capacity of 3860mAh / g. The lithium ion conductivity of the battery separator can be improved by replacing traditional ceramic materials (such as alumina, boehmite, etc.) with lithium aluminum titanium phosphate (LATP) materials with ion conductivity, but LATP is not in stable contact with the metal lithium negative electrode. In the process of contact between LATP and metal lithium, the structural stability of LATP is often destroyed, and side reaction products may also aggregate at the interface, thereby reducing the ionic conductivity of the interface. Therefore, solving the contact stability between LATP and metal lithium and improving the ionic conductivity of the separator are of great significance to improving the cycle performance of lithium metal batteries. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a battery separator and a preparation method thereof, which can effectively improve the ionic conductivity of the separator and the cycle performance of the metal lithium battery.

[0004] Therefore, in a first aspect of the present invention, the present invention provides a battery separator, characterized in that it comprises:

[0005] Base film, coating, the coating is located on at least one side of the base film; the coating comprises the following raw materials by weight:

[0006] Oxide electrolyte 100 parts;

[0007] 1 to 10 parts of polymer electrolyte;

[0008] 1 to 10 parts of amino-terminated polyethylene oxide.

[0009] The battery diaphragm coating of the present invention uses amino-terminated polyethylene oxide to coat an oxide electrolyte, which is used in combination with a polymer electrolyte. The oxide electrolyte is the main component of the battery diaphragm coating, and its function is to resist heat and improve the ionic conductivity of the diaphragm. The amino-terminated polyethylene oxide is coated on the surface of the oxide electrolyte as a coating agent to avoid direct contact between the oxide electrolyte and the metal lithium negative electrode, effectively isolating the oxide electrolyte to improve the lithium ion transmission performance, and improve the contact stability between the diaphragm and the metal lithium negative electrode. The amino group in the amino-terminated polyethylene oxide can combine with the ether bond of the polymer electrolyte polyethylene oxide to reduce the crystallinity of the polyethylene oxide. At the same time, the coating contains a large number of ether bonds, which can improve the ionic conductivity. As a result, the ionic conductivity of the lithium metal battery can be effectively improved, and the cycle performance of the lithium metal battery can be improved.

[0010] In some embodiments, the oxide electrolyte includes lithium aluminum titanium phosphate; the particle size D50 of the lithium aluminum titanium phosphate is 200-700 nm.

[0011] In some embodiments, the polymer electrolyte includes polyethylene oxide; the molecular weight of the polyethylene oxide is 300,000 to 600,000.

[0012] In some embodiments, the amino-terminated polyethylene oxide satisfies at least one of the following:

[0013] (1) The amino-terminated polyethylene oxide comprises at least two -NH2 groups;

[0014] (2) The amino-terminated polyethylene oxide comprises X -O-CH2CHCH3- groups and Y -O-CH2-CH2- groups (X is an integer of 3 to 6, and Y is an integer of 5 to 39);

[0015] (3) The molecular weight of the amino-terminated polyethylene oxide is 300 to 2000.

[0016] In some embodiments, the coating further comprises the following raw materials, by weight:

[0017] 1 to 5 parts of coupling agent;

[0018] 5-15 parts of other additives;

[0019] 100 to 400 parts of water.

[0020] In some embodiments, the coating satisfies at least one of the following:

[0021] (a) the coupling agent includes a silane coupling agent, and the silane coupling agent includes an epoxy group;

[0022] (b) Other additives include dispersants, binders and wetting agents; the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and polyvinyl alcohol; the binder includes at least one of polyacrylate, polyacrylate, polyvinyl alcohol and polyurethane; the wetting agent includes at least one of polyethylene glycol, sodium docusate, polyether-modified organosiloxane and fluorocarbon.

[0023] In a second aspect of the present invention, the present invention provides a method for preparing a battery separator, comprising the following steps:

[0024] mixing the polymer electrolyte with water to obtain a first solution;

[0025] Mixing water, a coupling agent, an oxide electrolyte, and amino-terminated polyethylene oxide to obtain a first dispersion;

[0026] Mixing the first solution with the first dispersion, adding other additives to form a mixed solution, filtering, and collecting the filtrate;

[0027] The filtrate is applied to at least one side of the base film to form a coating.

[0028] Therefore, the battery separator coating can improve the ionic conductivity of the separator and enhance the performance of metal lithium batteries.

[0029] In some embodiments, the preparation method includes the following raw materials, by weight:

[0030] Oxide electrolyte, 100 parts;

[0031] Polymer electrolyte, 1 to 10 parts;

[0032] Amino-terminated polyethylene oxide, 1 to 10 parts;

[0033] Coupling agent, 1 to 5 parts;

[0034] Other additives, 5-15 parts;

[0035] Water, 100-400 parts.

[0036] In some embodiments, the coating has a thickness of 1 to 5 μm.

[0037] In the third aspect of the present invention, the present invention provides a lithium metal battery, comprising the battery separator of the first aspect, or comprising the battery separator obtained by the preparation method of the second aspect.

[0038] Therefore, the lithium metal battery of the present invention has excellent ion conductivity and capacity retention rate.

[0039] Compared with the prior art, the present invention has the following beneficial technical effects:

[0040] (1) In the battery separator of the present invention, lithium aluminum titanium phosphate (LATP) is coated with terminal amino polyethylene oxide to avoid direct contact between LATP and the metal lithium negative electrode, thereby improving the contact stability between the battery separator and the metal lithium negative electrode.

[0041] (2) The amino group in the amino-terminated polyethylene oxide can combine with the ether bond in polyethylene oxide to reduce the crystallinity of polyethylene oxide. At the same time, the diaphragm coating contains a large number of ether bonds, which further improves the ionic conductivity.

[0042] (3) The battery separator preparation process of the present invention has the advantages of being environmentally friendly, simple in process, low in cost, and convenient for large-scale continuous production.

[0043] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0044] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0045] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0046] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0047] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0048] In a first aspect of an embodiment of the present invention, the present invention provides a battery separator, characterized in that it comprises:

[0049] Base film, coating, the coating is located on at least one side of the base film; the coating comprises the following raw materials by weight:

[0050] Oxide electrolyte 100 parts;

[0051] 1 to 10 parts of polymer electrolyte;

[0052] 1 to 10 parts of amino-terminated polyethylene oxide;

[0053] The battery diaphragm coating of the present invention adopts an oxide electrolyte coated with amino-terminated polyethylene oxide, which is used in combination with a polymer electrolyte. The oxide electrolyte is the main component of the battery diaphragm coating, and its function is to resist heat and improve the ionic conductivity of the diaphragm. The amino-terminated polyethylene oxide is used as a coating agent, which is coated on the surface of the oxide electrolyte to avoid direct contact between the oxide electrolyte and the metal lithium negative electrode, effectively isolating the oxide electrolyte to improve the lithium ion transmission performance, and improve the contact stability between the diaphragm and the metal lithium negative electrode. Other amino groups in the amino-terminated polyethylene oxide can combine with the ether bond of the polymer electrolyte polyethylene oxide to reduce the crystallinity of polyethylene oxide to improve the ionic conductivity. As a result, the ionic conductivity of the lithium metal battery can be improved, and the cycle performance of the lithium metal battery can be improved.

[0054] In some embodiments of the present invention, the oxide electrolyte includes lithium titanium aluminum phosphate, and the particle size D50 of the lithium titanium aluminum phosphate is 200-700 nm. Further, the particle size D50 is 300-500 nm.

[0055] According to an embodiment of the present invention, lithium aluminum titanium phosphate (LATP) is the main component of the battery separator coating, which plays a role in heat resistance and improving the ionic conductivity of the separator. The particle size D50 of LATP will affect the packing density of the coating, and then affect the thermal stability of the separator. In the range of particle size D50 of 300 to 500nm, when the particle size D50 is small, the packing density is large, which is beneficial to improve the thermal stability of the separator. When the particle size is large, the packing density is small, which is beneficial to improve the air permeability of the separator. Thus, the thermal stability of the separator is improved, and the cycle performance of the lithium metal battery is improved.

[0056] As an example, the particle size D50 of lithium aluminum titanium phosphate is 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, etc.

[0057] In some embodiments of the present invention, the polymer electrolyte includes polyethylene oxide; the molecular weight of the polyethylene oxide is 300,000 to 600,000.

[0058] According to the embodiments of the present invention, polyethylene oxide can provide ion conduction channels, improve battery safety, and improve ion conductivity. Polyethylene oxide can also synergistically act with amino-terminated polyethylene oxide to further improve ion conductivity.

[0059] As an example, the molecular weight of polyethylene oxide is 300,000, 350,000, 400,000, 450,000, 500,000, 600,000, etc.

[0060] In some embodiments of the present invention, the amino-terminated polyethylene oxide satisfies at least one of the following:

[0061] (1) The amino-terminated polyethylene oxide comprises at least two -NH2 groups;

[0062] (2) The amino-terminated polyethylene oxide comprises X -O-CH2CHCH3- groups and Y -O-CH2-CH2- groups (X is an integer of 3 to 6, and Y is an integer of 5 to 39);

[0063] (3) The molecular weight of the amino-terminated polyethylene oxide is 300 to 2000.

[0064] According to an embodiment of the present invention, amino-terminated polyethylene oxide is used as a coating agent and is coated on the surface of LATP through a coupling agent to prevent LATP from directly contacting the metal lithium negative electrode, effectively isolating LATP to improve the lithium ion transmission performance, and improving the contact stability between the diaphragm and the metal lithium negative electrode. In addition, the amino group in the amino-terminated polyethylene oxide can be combined with the ether bond of the polyethylene oxide in the polymer electrolyte to reduce the crystallinity of the polyethylene oxide. At the same time, the coating contains a large number of ether bonds, which can improve the ionic conductivity. Thus, the ionic conductivity and cycle performance of the lithium metal battery are improved.

[0065] As an example, the molecular weight of the amino-terminated polyethylene oxide is 300, 600, 900, 1200, 1500, 1800, 2000, etc.

[0066] In some embodiments of the present invention, the coating further comprises the following raw materials, measured in parts by weight:

[0067] 1 to 5 parts of coupling agent;

[0068] 5-15 parts of other additives;

[0069] 100 to 400 parts of water.

[0070] According to the embodiment of the present invention, the main function of the coupling agent is to make the coating agent coated on the surface of LATP through coupling. The epoxy group in the coupling agent molecule is bonded to an amino group of the amino-terminated polyethylene oxide, and the epoxy group is bonded to the oxide solid electrolyte. The main functions of other auxiliary agents are: the dispersant can prevent the sedimentation and agglomeration of particles in the coating liquid; the main function of the binder is to bond the coating to the surface of the base film; the main function of the wetting agent is to improve the spreadability of the coating liquid on the base film. As a result, the ionic conductivity and cycle stability of the lithium metal battery are improved.

[0071] In some embodiments of the present invention, the coating satisfies at least one of the following:

[0072] (a) the coupling agent includes a silane coupling agent, and the silane coupling agent includes an epoxy group;

[0073] (b) Other additives include dispersants, binders and wetting agents; the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and polyvinyl alcohol; the binder includes at least one of polyacrylate, polyacrylate, polyvinyl alcohol and polyurethane; the wetting agent includes at least one of polyethylene glycol, sodium docusate, polyether-modified organosiloxane and fluorocarbon.

[0074] As an example, the silane coupling agent includes KH560.

[0075] In some embodiments of the present invention, the added amount of the dispersant is 1 to 5 parts by weight; the added amount of the binder is 3 to 10 parts by weight; and the added amount of the wetting agent is 0.1 to 1 part by weight.

[0076] In a second aspect of the embodiment of the present invention, the present invention provides a method for preparing a battery separator, comprising the following steps:

[0077] mixing the polymer electrolyte with water to obtain a first solution;

[0078] Mixing water, a coupling agent, an oxide electrolyte, and amino-terminated polyethylene oxide to obtain a first dispersion;

[0079] Mixing the first solution with the first dispersion, adding other additives to form a mixed solution, filtering, and collecting the filtrate;

[0080] The filtrate is applied to at least one side of the base film to form a coating.

[0081] The preparation method of the present invention is simple and easy to operate, and has high preparation efficiency. The prepared battery separator can effectively improve the ion conductivity and cycle performance of lithium metal batteries.

[0082] In some embodiments of the present invention, the preparation method includes the following raw materials, measured by weight:

[0083] Oxide electrolyte, 100 parts;

[0084] Polymer electrolyte, 1 to 10 parts;

[0085] Amino-terminated polyethylene oxide, 1 to 10 parts;

[0086] Coupling agent, 1 to 5 parts;

[0087] Other additives, 5-15 parts;

[0088] Water, 100-400 parts.

[0089] In some embodiments of the present invention, the thickness of the coating is 1-5 μm.

[0090] According to an embodiment of the present invention, when the thickness of the coating is 1-5 μm, the lithium metal battery has excellent ion transport, low battery internal resistance, and good mechanical properties, thereby improving the ion conductivity of the lithium metal battery.

[0091] By way of example, the coating has a thickness of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.

[0092] In some embodiments of the present invention, the base film satisfies at least one of the following:

[0093] (1) The base film includes at least one of polyethylene (PE), polypropylene (PP), composite film, and non-woven fabric;

[0094] (2) The thickness of the base film is 5 to 20 μm.

[0095] In a third aspect of the embodiments of the present invention, the present invention provides a lithium metal battery, comprising the battery separator of the first aspect, or comprising the battery separator obtained by the preparation method of the second aspect.

[0096] Therefore, the lithium metal battery of the present invention has excellent ionic conductivity and cycle performance.

[0097] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0098] Embodiment 1:

[0099] (1) mixing 10 parts by weight of polyethylene oxide (PEO) (molecular weight 300,000) with 5 times its weight of deionized water, stirring evenly to obtain a first solution;

[0100] (2) 150 parts by weight of deionized water and 2 parts by weight of a silane coupling agent (KH560) were stirred evenly, and then 100 parts by weight of LATP (D50 particle size: 200 nm) was added and stirred evenly, and then 10 parts by weight of amino-terminated polyethylene oxide (X=3, Y=7) was added and stirred evenly to obtain a first dispersion;

[0101] (3) mixing the first solution and the first dispersion and sequentially adding 5 parts by weight of other additives (including 1.5 parts by weight of sodium carboxymethyl cellulose, 3.0 parts by weight of polyacrylate, and 0.5 parts by weight of polyether-modified organosiloxane), stirring evenly and filtering to collect the filtrate;

[0102] (4) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0103] Embodiment 2:

[0104] (1) mixing 7 parts by weight of polyethylene oxide (PEO) (molecular weight 400,000) with 10 times its weight of deionized water, stirring evenly to obtain a first solution;

[0105] (2) 130 parts by weight of deionized water and 3 parts by weight of a silane coupling agent (KH560) were stirred evenly, and then 100 parts by weight of LATP (D50 particle size: 500 nm) was added and stirred evenly, and then 1 part by weight of amino-terminated polyethylene oxide (X=6, Y=12) was added and stirred evenly to obtain a first dispersion;

[0106] (3) mixing the first solution and the first dispersion and sequentially adding 8 parts by weight of other additives (including 3 parts by weight of sodium carboxymethyl cellulose, 4.5 parts by weight of polyacrylate, and 0.5 parts by weight of polyether-modified organosiloxane), stirring evenly and filtering to collect the filtrate;

[0107] (4) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0108] Embodiment 3:

[0109] (1) mixing 3 parts by weight of polyethylene oxide (PEO) (molecular weight 500,000) with 10 times its weight of deionized water, stirring evenly to obtain a first solution;

[0110] (2) 270 parts by weight of deionized water and 1 part by weight of a silane coupling agent (KH560) were stirred evenly, and then 100 parts by weight of LATP (D50 particle size: 700 nm) was added and stirred evenly, and then 3 parts by weight of amino-terminated polyethylene oxide (X=3, Y=9) was added and stirred evenly to obtain a first dispersion;

[0111] (3) mixing the first solution and the first dispersion and sequentially adding 10 parts by weight of other additives (including 3 parts by weight of sodium carboxymethyl cellulose, 6 parts by weight of polyacrylate, and 1 part by weight of polyether-modified organosiloxane), stirring evenly and filtering to collect the filtrate;

[0112] (4) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0113] Embodiment 4:

[0114] (1) mixing 10 parts by weight of polyethylene oxide (PEO) (molecular weight 600,000) with 10 times its weight of deionized water, stirring evenly to obtain a first solution;

[0115] (2) 300 parts by weight of deionized water and 5 parts by weight of a silane coupling agent (KH560) were stirred evenly, and then 100 parts by weight of LATP (D50 particle size: 500 nm) was added and stirred evenly, and then 5 parts by weight of amino-terminated polyethylene oxide (X=6, Y=39) was added and stirred evenly to obtain a first dispersion;

[0116] (3) mixing the first solution and the first dispersion and sequentially adding 15 parts by weight of other additives (including 3 parts by weight of sodium carboxymethyl cellulose, 11 parts by weight of polyacrylate, and 1 part by weight of polyether-modified organosiloxane), stirring evenly and filtering to collect the filtrate;

[0117] (4) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0118] Comparative Example 1:

[0119] (1) mixing 7 parts by weight of polyethylene oxide (PEO) (molecular weight 400,000) with 10 times its weight of deionized water, stirring evenly to obtain a first solution;

[0120] (2) 130 parts by weight of deionized water and 100 parts by weight of LATP (D50 particle size: 500 nm) were stirred uniformly to obtain a first dispersion;

[0121] (3) mixing the first solution and the first dispersion and sequentially adding 8 parts by weight of other additives (including 3 parts by weight of sodium carboxymethyl cellulose, 4.5 parts by weight of polyacrylate, and 0.5 parts by weight of polyether-modified organosiloxane), stirring evenly and filtering to collect the filtrate;

[0122] (4) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0123] Comparative Example 2:

[0124] (1) 200 parts by weight of deionized water and 100 parts by weight of LATP (D50 particle size: 500 nm) were stirred uniformly to obtain a first dispersion;

[0125] (2) adding 10 parts by weight of other additives (including 3 parts by weight of sodium carboxymethyl cellulose, 6 parts by weight of polyacrylate, and 1 part by weight of polyether-modified organosiloxane) to the first dispersion in sequence, stirring evenly, filtering, and collecting the filtrate;

[0126] (3) The filtrate was coated on both sides of a 9 μm base film (PE), and dried to remove moisture to obtain a battery separator.

[0127] The composition of the battery separator raw materials of the above embodiments and comparative examples is shown in Table 1.

[0128] Table 1 Battery separator raw material composition formula of the embodiment and comparative example

[0129]

[0130]

[0131] Performance Test:

[0132] 1. Test Method

[0133] 1. Thickness test:

[0134] The thickness of the diaphragm product prepared in the present invention is directly tested at multiple points using a Mahr thickness gauge, and the average value is taken.

[0135] 2. Diaphragm ion conductivity test:

[0136] The electrochemical impedance spectra of the positive electrode shell / diaphragm / gasket / shrapnel / negative electrode shell samples were measured using an electrochemical workstation, and the ionic conductivity (σ) of the separator was calculated according to formula (1).

[0137] σ=d / (Rb*S)(1);

[0138] Where: σ is the ionic conductivity of the diaphragm, in S / cm; d is the thickness of the diaphragm, in μm; Rb is the resistance of the diaphragm, in Ω; S is the area of ​​the stainless steel sheet, in cm 2 .

[0139] 3. Lithium metal battery cycle performance test:

[0140] The assembly system is NGM523 / metal lithium liquid battery, and the diaphragm coating contacts the metal lithium negative electrode. The charge and discharge cycle test is carried out using Blue Electric equipment, and the cycle rate is 0.2C / 0.2C.

[0141] 2. Test Results

[0142] The battery separator performance test results of all the above embodiments and comparative examples are shown in Table 2.

[0143] Table 2 Battery separator performance test results of the embodiments and comparative examples

[0144]

[0145] In summary, it can be seen from Table 2 that in the diaphragms of Examples 1-4, LATP is coated with amino-terminated polyethylene oxide and acts synergistically with PEO, so the ionic conductivity and capacity retention rate of Examples 1-4 are better than those of the comparative example.

[0146] In Comparative Example 1, LATP is mixed with PEO and LATP lacks the amino-terminated polyethylene oxide coating, resulting in direct contact between LATP and the metal lithium negative electrode, causing the metal lithium to transfer Ti in LATP to the negative electrode. 4+ Reduction to Ti 3+ , destroying the structural stability of LATP, thereby reducing the ionic conductivity and capacity retention rate of the interface. In Comparative Example 2, the diaphragm coating is a separate LATP coating, which also leads to direct contact between LATP and the metal lithium negative electrode. Therefore, it is shown that the coating of LATP with terminal amino polyethylene oxide can effectively isolate LATP from direct contact with the metal lithium negative electrode, and synergize with PEO to improve the ionic conductivity and capacity retention rate of the lithium metal battery.

[0147] This indicates that the battery separator of the present invention can effectively improve the ionic conductivity of lithium metal batteries and enhance the battery cycle performance.

[0148] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0149] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A battery separator, characterized in that: include: Basement membrane, A coating, the coating being located on at least one surface of the base film; the coating comprising the following raw materials in parts by weight: Oxide electrolyte 100 parts; 1 to 10 parts of polymer electrolyte; 1 to 10 parts of amino-terminated polyethylene oxide.

2. The battery separator according to claim 1, characterized in that: The oxide electrolyte includes lithium aluminum titanium phosphate; the particle size D50 of the lithium aluminum titanium phosphate is 200-700 nm.

3. The battery separator according to claim 1, characterized in that: The polymer electrolyte includes polyethylene oxide; the molecular weight of the polyethylene oxide is 300,000 to 600,000.

4. The battery separator according to claim 1, characterized in that: The amino-terminated polyethylene oxide satisfies at least one of the following: (1) The amino-terminated polyethylene oxide comprises at least two -NH2 groups; (2) The amino-terminated polyethylene oxide comprises X -O-CH2CHCH3- groups and Y -O-CH2-CH2- groups (X is an integer of 3 to 6, and Y is an integer of 5 to 39); (3) The molecular weight of the amino-terminated polyethylene oxide is 300 to 2000.

5. The battery separator according to claim 1, characterized in that: The coating further comprises the following raw materials by weight: 1 to 5 parts of coupling agent; 5-15 parts of other additives; 100 to 400 parts of water.

6. The battery separator according to claim 5, characterized in that: The coating satisfies at least one of the following: (a) the coupling agent comprises a silane coupling agent, and the silane coupling agent comprises an epoxy group; (b) The other auxiliary agents include dispersants, binders and wetting agents; the dispersant includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and polyvinyl alcohol; the binder includes at least one of polyacrylate, polyacrylate, polyvinyl alcohol and polyurethane; the wetting agent includes at least one of polyethylene glycol, sodium docusate, polyether-modified organosiloxane and fluorocarbon.

7. A method for preparing a battery separator, characterized in that: The following steps are involved: mixing the polymer electrolyte with water to obtain a first solution; Mixing water, a coupling agent, an oxide electrolyte, and amino-terminated polyethylene oxide to obtain a first dispersion; mixing the first solution with the first dispersion, adding other additives to form a mixed solution, filtering, and collecting the filtrate; The filtrate is applied to at least one side of the base film to form a coating layer.

8. The preparation method according to claim 7, characterized in that: By weight, it includes the following raw materials: Oxide electrolyte, 100 parts; Polymer electrolyte, 1 to 10 parts; Amino-terminated polyethylene oxide, 1 to 10 parts; Coupling agent, 1 to 5 parts; Other additives, 5-15 parts; Water, 100-400 parts.

9. The preparation method according to claim 7, characterized in that: The coating has a thickness of 1 to 5 μm.

10. A lithium metal battery, characterized in that: The invention comprises the battery separator according to any one of claims 1 to 6, or the battery separator obtained by the preparation method according to any one of claims 7 to 9.